2017
DOI: 10.1097/sla.0000000000001614
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Canadian Trauma Systems

Abstract: We observed significant variation in trauma center mortality across Canadian provinces, specifically for severe traumatic brain injury. Provinces with more recommended trauma system components had better patient survival. Results suggest that trauma system configuration may be an important determinant of injury mortality. A better understanding of which system processes drive optimal outcomes is required to reduce the burden of injury worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…In situations when oral agents cannot be administered or there are concerns about absorption, the use of an intravenous glycoprotein IIb/IIIa inhibitor or the recently available intravenous P2Y 12 inhibitor cangrelor can be considered.…”
Section: Suggestions For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In situations when oral agents cannot be administered or there are concerns about absorption, the use of an intravenous glycoprotein IIb/IIIa inhibitor or the recently available intravenous P2Y 12 inhibitor cangrelor can be considered.…”
Section: Suggestions For Clinical Practicementioning
confidence: 99%
“…In addition, studies have demonstrated poor gastrointestinal absorption of these medications in the setting of MI, a problem that may be exacerbated in CS. 188 The ISAR-SHOCK (Efficacy Study of LV Assist Device to Treat Patients With Cardiogenic Shock) registry, which included patients with CS undergoing PCI who had a platelet function assessment after receiving an oral P2Y 12 inhibitor, reported that prasugrel was associated with a nonsignificant reduction in 30-day mortality. 188 In a secondary analysis of the IABP-SHOCK II trial, there was no difference in mortality or bleeding events in a comparison of clopidogrel, prasugrel, and ticagrelor in patients with acute MI complicated by CS.…”
Section: Antithrombotic Pharmacotherapy Adjuncts To Pcimentioning
confidence: 99%
“…Mortality rates have decreased in the last decades, largely due to improvements in trauma systems and supportive critical care [29]. Yet, case fatality rates in severe TBI have not decreased significantly since 1990 [30], remaining with an outstanding mortality, because up to 50% of the patients will still die and nearly all survivors will present some degree of sequelae [3,4,6,[31][32][33]. To the present, regardless of over dozens of phase III clinical trials, there are no specific treatments known to improve TBI outcomes [13].…”
Section: Tbi Is Classified By Different Methods; In the 1970s Teasdamentioning
confidence: 99%
“…Previous analyses of the same data showed no significant changes in benchmarking results when deaths were included in a competitive risks framework. 5 The research ethics board of the CHU de Québec approved our study.…”
Section: Patientsmentioning
confidence: 99%
“…[1][2][3] However, variations in patient outcomes have been observed even among level I trauma centres in the United States 4 and Canada, 5 and suboptimal quality of care has been documented in up to 50% of trauma system admissions. 6,7 Research has suggested that benchmarking activities stimulate quality improvement, which in turn improves patient outcomes.…”
mentioning
confidence: 99%